2019
DOI: 10.3390/agronomy9020055
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Seed Yield, Mineral Nutrients and Soil Properties of Sesame (Sesamum indicum L.) as Influenced by Biochar Addition on Upland Field Converted from Paddy

Abstract: Sesame is an important oilseed crop cultivated worldwide. However, research has focused on biochar effects on grain crops and vegetable and there is still a scarcity of information of biochar addition on sesame. This study was to assess the effect of biochar addition on sesame performance, with a specific emphasis on growth, yield, leaf nutrient concentration, seed mineral nutrients, and soil physicochemical properties. A field experiment was conducted on an upland field converted from paddy at Tottori Prefect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 66 publications
0
13
0
1
Order By: Relevance
“…Biochar (BC) is an organically active soil amendment with very high soil pore volume and cation exchange capacity and has been reported to reduce drought stress in plants [31][32][33][34]. Biochar is a nutrient-rich, black carbon soil amendment [35] that is produced through pyrolysis of waste feedstock at high temperature [36] under anaerobic or partially anaerobic condition [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar (BC) is an organically active soil amendment with very high soil pore volume and cation exchange capacity and has been reported to reduce drought stress in plants [31][32][33][34]. Biochar is a nutrient-rich, black carbon soil amendment [35] that is produced through pyrolysis of waste feedstock at high temperature [36] under anaerobic or partially anaerobic condition [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not focus on other benefits of biochar, this could be attributed to the biochar increasing other nutrients such as N, apart from the large quantities of K than inorganic fertilizer, detoxifying phytotoxic compounds from continuously monocropped soils and thereby improving sesame seedling growth [16,35]. Furthermore, the high CEC of the biochar and the increase in soil CEC in the biochar balancing treatment is an indicator of nutrient retention for sesame growth suggesting that rice husk biochar could improve soil nutrient status in continuous monocropping [16]. Therefore, the rice husk biochar addition could be recommended for improving sesame growth to alleviate the imbalances in soil exchangeable cations on continuously monocropped soils where K is a limiting factor.…”
Section: Discussionmentioning
confidence: 99%
“…Biochar is a soil amendment produced from thermal degradation of organic materials through the process of pyrolysis and can supply a high amount of potassium [14,15]. Recently, we reported that rice husk biochar improved sesame growth through increasing soil exchangeable K and improving K nutrition on an upland field converted paddy in Japan [16]. However, there is lack of information on the use of biochar material and inorganic fertilizers to balance soil exchangeable cations in deteriorated soils from continuous monocropping fields.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of sesame seeds, the production of sesame in Japan had been on a negligible scale although it is gradually increasing, especially on abandoned paddy fields [5,6]. However, we previously reported yield decline of sesame on upland fields converted from paddy fields under intensive continuous monocropping as a result of changes in soil nutrient availability [7].…”
Section: Introductionmentioning
confidence: 94%